Fecal Microbial Therapy – Promises and Pitfalls - Merenstein, Daniel (J Pediatr Gastroenterol Nutr, 2014)
A rapidly-expanding range of diverse human diseases are now associated with perturbations to the gastrointestinal microbiome. Fecal microbial transfer (FMT) has been used with high rates of efficacy to treat gastrointestinal microbiome perturbation associated with recurrent Clostridium difficile infection, and is now being considered for other indications. Here we discuss the gut microbiome, review published and on-going studies using FMT as a treatment modality for human disease, consider the regulatory aspects of FMT and outline some factors that should be considered in cases where this therapeutic strategy is being contemplated.